Design of the filling device for citrus seedling pot based on turnover box - Xu, Qinchao; Chen, Haoyi; Liu, Chuanxin; Zhu, Jiating; Li, Shanjun; Ye, Meiqi (International Journal of Agricultural and Biological Engineering, 2025)
In China, soft plastic pots are the predominant container used for the cultivation of citrus seedlings. However, due to their soft characteristics, manual operation is the primary method of pot filling and placement, which significantly impedes production efficiency. In order to resolve this issue, a solution for filling citrus seedling pots based on a turnover box was proposed. By analyzing the movement status of the turnover box unloading mechanism, the length of each component was calculated, and the specific structure of the turnover box was designed. The substrate lifting rate of the conveyor belt was analyzed and the structural parameters of the lifting mechanism were determined. Through theoretical analysis of the substrate trajectory during the dispersion process, the inlet position of the splitter mechanism was determined, and the specific structure of the splitter mechanism was designed to control the uniformity of the substrate distribution. A seedling pot filling process simulation model was constructed using discrete element software. The operating parameters of the filling device were evaluated, and the filling effect was analyzed. The test prototype was processed and three loading tests were carried out. The results show that the prototype runs stably, with a loading time of 8 s for 16 pots. The unloading mechanism of the turnover box is reliable, and the seedling pots are neatly arranged after unloading. The maximum weight among the 16 pots in the turnover box is 2.00 kg, while the minimum weight is 1.88 kg. The mean weight is 1.94 kg, with a coefficient of variation of 2.47%. The excess substrate mass scraped on the turnover box is 0.83 kg, accounting for 2.67% of the total mass of the 16 pots. The prototype design is reasonable, with good filling uniformity and high efficiency. The research results can provide reference for the development and optimization of citrus seedling pot filling and transportation equipment in the future. Keywords: agricultural machinery, citrus, seedling pot, turnover box, filling, EDEMDOI: 10.25165/j.ijabe.20251803.9397Citation: Xu Q C, Chen H Y, Liu C X, Zhu J T, Li S J, Ye M Q. Design of the filling device for citrus seedling pot based on turnover box. Int J Agric & Biol Eng, 2025; 18(3): 97–104.